LIQUISOLID TECHNIQUE FOR DISSOLUTION AND BIOAVAILABILITY ENHANCEMENT OF POORLY SOLUBLE DRUGS - Magdum, Shrikant S. (Universal Journal of Pharmaceutical Research, 2017)
Liquisolid formulations have attracted substantial interest as an efficient means of improving the dissolution and ultimately bioavailability. The technique is based upon the admixture of drug loaded solutions with appropriate carrier, coating materials and use of non-volatile solvent causes improved wettability. The inclusion complexes of drug with beta cyclodextrin (βCD) were formulated by kneading method and highest solubility complex was further used for preparation of liquisolid formulation to get synergistic effect. Also it raises drug incorporation with dissolution enhancement compared with conventional formulation. There are various techniques for bioavailability enhancement, such as altering the pharmacokinetic parameters, inhibition of enzyme etc. For this purpose some herbal inhibitors can be used; ex piperine. The prepared formulations were characterized by FTIR, DSC, PXRD and in vitro dissolution studies. Hence, this liquisolid technique with two way approach of solubility and bioavailability enhancement may found as key aspect in designing of formulations. Peer Review History: Received 16 August 2017; Revised 14 September; Accepted 26 October; Available online 15 November 2017 Academic Editor: Dr. Asia Selman Abdullah , Al-Razi university, Department of Pharmacy, Yemen, asia_abdullah65@yahoo.com Reviewer(s) detail: Dr. Leyla Açık , Gazi University, Ankara, Turkey, leylaacik@gmail.com Dr. Emmanuel O. Olorunsola , Department of Pharmaceutics & Pharmaceutical Technology, University of Uyo, Nigeria, olorunsolaeo@yahoo.com